Kemitraan Masyarakat untuk Pemulihan Pasca Operasi Caesar: Berbagi pengetahuan dan Dukungan dalam Perawatan Setelah Persalinan: Community Partnership for Post-Caesarean Section Recovery: Sharing knowledge and Support in Postpartum care - Zuhana, Nina; Aisyah, Risqi Dewi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Sectio cesarean section has a significant impact on the quality of life of mothers and children in the long term. Mothers undergoing SC require additional health care and a more intensive rehabilitation process due to complications that may arise during the procedure. Postpartum mothers' independence in self-care is influenced by many factors, one of which is knowledge and support from those closest to them. The purpose of this community service activity is to assist partners in SC's post-operative recovery efforts. The method used is to provide education about the importance of postoperative postoperative postoperative postpartum care and the support of those closest to you in postoperative recovery. The results obtained from this activity were a significant increase in the average knowledge between before and after the provision of education, which was 20.15. The average knowledge before being given education was 70.40 and after being given education, the average score was 90.55. This shows positive results It is necessary to carry out structured and routine continuous education activities for postpartum mothers and their families so that they have a deep understanding of postoperative care for cesarean section.